(untitled) (Nigerian Journal of Technology, 2020)
In this study, incessant collapse of water infrastructure along with shortage of water supply from public mains due to poor maintenance culture within the coastal areas of Akwa Ibom State are the key issues and challenges associated with the performance of water infrastructure in the area under consideration. These indices have been of great concern to building services engineers, estate managers and other stakeholders within the built environment. With the option of continuous (periodic) and practical maintenance culture as a panacea, effective water supply is guaranteed. This study has established better ways of tackling these problems (indicative risks) concerning maintainability of water infrastructure for optimum service delivery. Qualitative analyses were performed on air and water samples collected within the affected water infrastructure environment. In this case, concrete water stanchions (CWS) and steel water stanchions (SWS) along with the mechanical systems: submersible pumps, control valves performance were also evaluated to ascertain the level of environmental damages meted on the water works over a period of time upon commissioning and use. From the achievable tests, it is evident that the pH (-) results are higher in the investigated CWS than SWS except the turbidity results which are at par. These results have demonstrated that CWS is preferable to SWS for ease of periodic maintenance. http://dx.doi.org/10.4314/njt.v39i3.33